Penggunaan integrasi moodle science learning berbasis proyek pada tema kebisingan kota - Yeni Widiyawati; Dwi Septiana Sari; Mohammad Masykuri; Cucuk Wawan Budiyanto; Indri Nurwahidah (Postgraduate, University of Mataram, 2022)
This study aims to determine the use of project-based Moodle science learning integration on the city noise theme. The type of research used is descriptive qualitative. The research was conducted in three junior high schools in the city of Semarang in the even semester of the 2020-2021 academic year. Based on the results of the study, teachers in each school responded positively to the use of Moodle science learning integration with the theme of city noise because the content in it was following the needs of teachers in science learning. In the first and second project assignments, there were only 10 students each who submitted their assignments. Based on the results of the study, it can be concluded that the use of project-based Moodle science learning integration on the theme of city noise is following the needs of science learning in schools, but has not been able to increase student activity optimally in the science learning process. Constraints found in the use of project-based integration of moodle science learning on the theme of city noise online are limited infrastructure, internet quota, learning time, low student interest and motivation, and lack of parental supervision in the implementation process